Isoflurane Sedation in Patients Undergoing Venoarterial Extracorporeal Membrane Oxygenation Treatment for Cardiogenic Shock—An Observational Propensity-Matched Study. (March 2020) - Scherer, Clemens; Kupka, Danny; Stocker, Thomas J; Joskowiak, Dominik; Scheuplein, Hanna; Schönegger, Carmen Maria; Born, Frank; Stremmel, Christopher; Lüsebrink, Enzo; Stark, Konstantin; Orban, Mathias; Petzold, Tobias; et al.
Abstract : Objectives: The feasibility and hemodynamic effects of isoflurane sedation in cardiogenic shock in the presence of venoarterial extracorporeal membrane oxygenation treatment are currently unknown. Design: Retrospective single-center study. Setting: Cardiac ICU of Munich university hospital. Patients/Subjects: Cardiogenic shock patients with venoarterial extracorporeal membrane oxygenation treatment under sedation with volatile isoflurane between November 2018 and October 2019 have been enrolled in this study and were matched by propensity score in a 1:1 ratio with IV sedated patients treated between January 2013 and November 2018 from the cardiogenic shock registry of the university hospital of Munich. Measurements and Main Results: Isoflurane sedation was used in 32 patients with cardiogenic shock and venoarterial extracorporeal membrane oxygenation treatment. The mean age of conventionally sedated patients was 58.4 ± 13.8 years and 56.3 ± 11.5 years for patients with isoflurane sedation ( p = 0.51). Administration of isoflurane was associated with lower IV sedative drug use during venoarterial extracorporeal membrane oxygenation treatment (86% vs 32%; p = 0.01). Mean systolic arterial pressure was similar (94.3 ± 12.6 vs 92.9 ± 10.5 mm Hg; p = 0.65), but mean heart rate was significantly higher in the conventional sedation group, when compared with the isoflurane group (85.2 ± 20.5 vs 74.7 ± 15.0 beats/min; p = 0.02). Catecholamine doses, venoarterial extracorporeal membrane oxygenation blood and gas flow, ventilation time (304 ± 143 vs 398 ± 272 hr; p = 0.16), bleeding complications bleeding academic research consortium 3a or higher (59.3% vs 65.3%; p = 0.76), and 30-day mortality (59.2% vs 63.4%, p = 0.80) were similar in both groups. The overall sedation costs per patient were significantly lower in the conventional group, when compared with the isoflurane group (537 ± 624 vs 1280 ± 837 [Euro sign]; p < 0.001). Conclusions: Volatile sedation with isoflurane is feasible—albeit at higher costs—in patients with cardiogenic shock and venoarterial extracorporeal membrane oxygenation treatment and was not associated with higher catecholamine dosage or extracorporeal membrane oxygenation flow rate compared with IV sedation.